2023
DOI: 10.3390/fishes8070333
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Curcumin/Chitosan Modulates Growth, Biochemical, Immune, and Antioxidative Profiles, and the Expression of Related Genes in Nile tilapia, Oreochromis niloticus

Abstract: This study aimed to evaluate the effects of dietary supplementation with nano-curcumin (NCur) and a nano-curcumin/chitosan blend (NCur/Ch) on growth performance, digestibility, immune response, antioxidant status, intestinal morphometric characters, and gene regulation in Nile tilapia. Fish (n = 180, initial body weight = 12.0 ± 0.53 g) received supplementary NCur at rates of 0 (control), 0.00625, and 0.0125, and NCur/Ch at rates of 0.00625 + 0.5 g/kg diet for 4 weeks. Growth performance parameters (final weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…The AFM had a study area of 300 nm × 300 nm and used an Al tip in contact mode and vacuum conditions. Thin film formation needed to be performed first via the free precipitation of the samples on mica plates [ 28 ]. The size was measured using dynamic light scattering (DLS).…”
Section: Methodsmentioning
confidence: 99%
“…The AFM had a study area of 300 nm × 300 nm and used an Al tip in contact mode and vacuum conditions. Thin film formation needed to be performed first via the free precipitation of the samples on mica plates [ 28 ]. The size was measured using dynamic light scattering (DLS).…”
Section: Methodsmentioning
confidence: 99%
“…discerned that synbiotic additions, combining Lactobacillus acidophilus with fructo oligosaccharides and mannan oligosaccharides, to the Nile tilapia diet amplified IGF-1 gene expression. Furthermore, In the research byElabd et al (2023), Nile tilapia that received dietary chitosan combined with nano-curcumin showed an up-regulation in the IGF-I expression level. Echoing these findings, our study also identified that GH and IGF-I gene expression levels in chitosan treatments surpassed that of the control.…”
mentioning
confidence: 96%
“…IGF-1 can stimulate amino acid absorption and protein synthesis in muscles and also slow down protein breakdown in muscle fibers (Liu et al, 2008). While numerous studies have dissected growth stimulators' impact on fish growth-related gene expression (Elabd et al, 2023;Hassaan et al, 2015;Safari et al, 2020), a discernible knowledge gap persists concerning chitosan's specific influence.…”
mentioning
confidence: 99%